Integrated management of chilli die back and anthracnose in Delhi region - M.GOPAL*; L.N. KADU, PRATIBHA SHARMA, G. KULSHRESTHA*, (Indian Phytopathology, 2004)
Three different pest management modules including biological, chemical and IPM were evaluated based on the epidemiology of chilli die-back and fruit rot on two cultivars of chilli viz. Pusa sadabhar (local) and Navjyoti (Hybrid). IPM module was found superior to biological and chemical module for managing the disease by 63.98 and 68.66% for die-back and fruit rot, respectively in Pusa sadabhar followed by chemical module with the disease control of 53.58 and 45.58 %, for die-back and fruit rot. The disease reduction was highest in IPM module followed by chemical module and biological but was significantly superior to control. In the variety Pusa sadabhar the percent disease control was higher than variety Navjyoti. These modules significantly increased the yield over control with the highest yield in IPM module. An effort has been made to highlight the status of different grain markets of Punjab state with regards to Karnal bunt (KB). Less affected areas during the last 11 years ( 1994-2004) from where wheat may be procured for export either by segregation at the grain market level or by contract farming are identified. Year to year variations occur in the disease as is evident from the percent KB - free samples recorded in different years. Amongst different districts, the disease was least in Patiala where av. KB – free samples were 85 % followed by samples from Amritsar (81.12%). Av. KB-free samples were as high as 90 % and above in seven grain markets in Punjab (Amritsar, Kotshmeer, Bagharian, Delhon, Muktsar, Bhadson and Bhasor).